ANALISIS PERAN SEKTOR PERTAMBANGAN DARI KABUPATEN TERHADAP PEREKONOMIAN KALIMANTAN TENGAH - Anta Lutfi Ana; Lausanne Dwi Nove Ompusunggu, Sri Wiyanti, Pebrianti, Akhmad Bakri, Suherman (CV. Adiba Aisha Amira, 2024)
Central Kalimantan Province is a province that has a potential mining sector, one of which is in Murung Raya Regency. Mining in Central Kalimantan has a very important role for the growth of the Central Kalimantan regional economy. We can see this in the data of the Central Kalimantan statistical center (BPS) from 2013-2022. The purpose of this study is to determine which districts are the mining base for Central Kalimantan. The analysis method we use is Location Quotient (LQ) analysis, the data used in this research is secondary data. The results of the Location Quotient analysis show that the mining database sector is located in 5 districts, namely, Murung Raya Regency, North Barito Regency, East Barito Regency, South Barito Regency, and Kapuas Regency.